An adolescent case of xeroderma pigmentosum variant confirmed by the onset of sun exposure‐related skin cancer during Crohn's disease treatment. Issue 1 (20th April 2018) - Terada, Aoi; Aoshima, Masahiro; Tanizaki, Hideaki; Nakazawa, Yuka; Ogi, Tomoo; Tokura, Yoshiki; Moriwaki, Shinichi
Abstract: The patient was a 16‐year‐old boy who was diagnosed with Crohn's disease at 13 years of age, who was treated with mesalazine, azathioprine, and infliximab. Concurrently, the patient developed small freckle‐like pigmented spots on sun‐exposed areas, which gradually increased in number. At 14 and 16 years of age, a blue‐gray macule and a nodule appeared on his face, respectively. A histopathological examination revealed that the macule had only postinflammatory pigmentation, while the nodule was basal cell carcinoma. The sensitivity to UV‐killing by colony formation of the patient's cells was normal but was enhanced by caffeine treatment. In addition, a pathologic mutation in the POLH gene was identified and a diagnosis of xeroderma pigmentosum variant (XP‐V) was established. XP‐V is a cutaneous type of XP that is commonly diagnosed from middle age after the induction of skin cancer on sun‐exposed areas. Our patient had a genetically sensitive background (XP‐V), and we considered that immunosuppressive agents for Crohn's disease may have enhanced the photocarcinogenesis at a young age. This finding implies that we should be careful about a skin cancer production and that protection from UV may be essential when pediatric patients with a genetic background of UV sensitivity take immunosuppressive agents. Abstract : The XP‐V patient reported here had BCC during the treatment for Crohn's disease at much younger age (16 y.o.) compared to other Japanese XP‐V cases (41 y.o.). He had a genetically UV‐sensitive background; XP‐V and we considered that immunosuppressive agents for Crohn's disease may have enhanced the photocarcinogenesis in this case. We think that this is an enlightening and important case report, suggesting that we should be careful about a skin cancer production and that more rigorous photoprotection may be essential when pediatric patients with a genetic background of UV sensitivity take immunosuppressive agents.